Functional properties of milk protein concentrate and micellar casein concentrate as affected by transglutaminase treatment. (April 2023) - Salunke, P.; Metzger, L.E.
Abstract: Milk protein concentrate (MPC) and micellar casein concentrate (MCC) are used in foods to increase protein content and improve functional properties. The use of cross-linking enzymes such as transglutaminase (TGase) has the potential to modify the physical properties of MPC or MCC and may improve their functional properties. The objective of this study was to determine the effect of TGase treatment of MPC and MCC retentates on the functionality of MPC and MCC. MCC and MPC retentates were produced and treated with TGase enzyme at three levels, namely 0.0 TGase addition (control), 0.3 units/g of protein, and 3.0 units/g of protein. Treated retentates were then spray dried and various functional properties, including water (WAC) and fat (FAC) absorption capacity, alcohol (AS) and heat (HS) stability, solubility, solubility index (SI), effect of calcium chelating salts, and glucono-δ-Lactone (in yogurt like formulation) were tested. MPC samples had significantly ( P  ≤ 0.05) higher AS, HS, solubility, higher yogurt viscosity, water holding capacity (WHC), and syneresis, and significantly ( P  ≤ 0.05) lower SI, WAC, and FAC as compared with respective MCC treatments. TGase treatment significantly increased the AS, HS, SI, and significantly ( P  ≤ 0.05) decreased solubility. In MCC yogurt samples, there was a significant ( P  ≤ 0.05) decrease in rapid visco analyzer viscosity, WHC, and syneresis as enzyme levels increased. The effect of calcium chelating salts was more pronounced at a higher TGase level. The study demonstrates that TGase treatment will significantly affect and modify the functionality of MCC and MPC. Graphical abstract: Image 1 Highlights: Milk protein concentrate (MPC) and micellar casein concentrate (MCC) affect certain functional properties. Transglutaminase (TGase) modifies the surface properties of casein micelle impacting, certain functional properties. TGase treatment in MPC and MCC makes milk proteins insoluble and delays denaturation. TGase treatment in MPC and MCC also delays gel formations with acid and delays the chelation action of emulsifying salts. With the right degree of crosslinking, the functionality of the MPC and MCC can be tailored to suit industry needs.